Pengaruh Elevasi Kepala 30 Derajat Terhadap Nilai Saturasi Oksigen Pasca Ekstubasi Dalam Pada Pasien Anestesi Umum - Nabilah Fathiyah Rahmah; Yustiana Olfah; Agus Sarwo Prayogi; Furaida Khasanah (POLTEKKES KEMENKES YOGYAKARTA, 2024)
Background: Extubation is an essential procedure in the termination of general anesthesia. Deep extubation is a comfortable option for patient but carries a higher risk of collapse and airway obstruction. Airway obstruction if not treated immediately will cause hypoxia which is the most common cause of death in anesthesia which is characterized by a decrease in oxygen saturation. Oxygenation therapy is not considered insufficient to prevent hypoxia, so combination of alternatives such as position management is needed to maintain airway patency. Objective: To determine the effect of head elevation 30 degrees on oxygen saturation post deep extubation in general anesthesia patients. Method: This research is a quantitative research using quasi-experimental method with pretest-posttest control group design. The study population included all orotracheal and nasotracheal general anesthesia patients who were deeply extubated. This study used consecutive sampling technique with 70 respondents divided into intervention group (head elevation 30 degrees) and control group (supination). This research was conducted in the recovery room at PKU Muhammadiyah Hospital Yogyakarta from February to April 2024. Results: The results showed that post deep extubation oxygen saturation given in the head elevation 30 degrees group had a mean result of 99.29 and in supination group got 97.86 where there was a better increase oxygen saturation if the patient post general anesthesia deep extubation in a head elevation 30 degree for 15 minutes compared to supination. Conclusion: There is an effect of head elevation 30 degrees on oxygen saturation post deep extubation in patients under general anesthesia.